Fuel cell performance and durability investigation of bimetallic radical scavengers in Aquivion® perfluorosulfonic acid membranes. (16th November 2017) - D'Urso, C.; Oldani, C.; Baglio, V.; Merlo, L.; Aricò, A.S.
Abstract: In this paper, we present a straightforward synthesis of bimetallic radical scavengers supported onto silica and an evaluation of their effectiveness to increasing the lifetime of Aquivion ® PFSA membranes. Such scavengers comprise cerium (Ce) and chromium (Cr) and were incorporated in e-PTFE reinforced thin membranes through suspension in water-based Aquivion ® PFSA dispersion. The bimetallic samples were physico-chemically characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) and Energy Dispersive X-ray (EDX) analyses and compared to the monometallic Ce and Cr scavengers prepared in the same way. The membranes containing the mono- or bi-metallic scavengers were electrochemically investigated in terms of polarization behavior, cell resistance and durability. The MEA based on monometallic Ce-based scavenger showed the largest durability (7-time more than a reference MEA). The bimetallic scavenger appears also very promising. However, a proper optimization of the composition is required for its application in highly durable composite Aquivion ® membrane. Highlights: Bimetallic (Ce and Cr) radical scavengers supported onto silica were synthesized. The bimetallic scavenger was loaded in ePTFE reinforced Aquivion ® PFSA membranes. The composite membrane showed a higher stability than a scavenger-free membrane.